2007
DOI: 10.1007/s11270-007-9451-8
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Attachment of Escherichia coli to Different Particle Size Fractions of an Agricultural Grassland Soil

Abstract: This study reports on the attachment preference of a faecally derived bacterium, Escherichia coli, to soil particles of defined size fractions. In a batch sorption experiment using a clay loam soil it was found that 35% of introduced E. coli cells were associated with soil particulates >2 μm diameter. Of this 35%, most of the E. coli (14%) were found to be associated with the size fraction 15-4 μm. This was attributed to the larger number of particles within this size range and its consequently greater surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 27 publications
7
63
2
Order By: Relevance
“…There was a 40% increase in the population of E. coli over the 10 h period, but only a 5% increase in the population of E. coli during the first 2 h (data not shown). Thus, we assume growth or die-off of E. coli during our 30 min experiments is negligible, which is consistent with Oliver et al (2007) .…”
Section: Experimental Designsupporting
confidence: 85%
See 1 more Smart Citation
“…There was a 40% increase in the population of E. coli over the 10 h period, but only a 5% increase in the population of E. coli during the first 2 h (data not shown). Thus, we assume growth or die-off of E. coli during our 30 min experiments is negligible, which is consistent with Oliver et al (2007) .…”
Section: Experimental Designsupporting
confidence: 85%
“…This means that the error of concentration of clay measured by the spectrometer was amplified by 5 or 10 times in the final results, while the error of the concentration of E. coli measured by counting the colony-forming units in the plates was amplified by 20 × 50 = 10 0 0 times. And the dilution ratio had to be adjusted frequently from experiment to experiment as well as sample to sample in order to keep the CFU counts within method-approved ranges ( Oliver et al, 2007 ). Indeed, the plate counting is especially imprecise when trying to relate it to a mass of E. coli ( Hedges, 2002;Oliver et al, 2005 ).…”
Section: Noisy Ecoli Datamentioning
confidence: 99%
“…As watershed size increases, so does the distance between land applied FIB sources and water monitoring points. This increased travel distance increases the opportunities for FIB losses due to sedimentation and entrapment of particle associated FIB, infiltration of runoff, and FIB decay [38][39][40][41]. A study conducted by Tian, et al [42] found that the delivery ratio of FIB to a stream increases as the distance decreases between the FIB source and the stream.…”
Section: Watershed Areamentioning
confidence: 99%
“…Particles of [2000 lm with a rapidly decomposing rate, were predominantly consisted to be particulate residues from plant materials. Several methods, such as repeated washing of soil aggregates and techniques based on soil physical fraction, were applied to study the distribution of SOM, microorganisms as well as enzyme activities relating to carbon (C) and nutrient cycling [nitrogen (N) and phosphorus (P)] in soil matrix (Allison and Jastrow 2006;Kanazawa and Filip 1986;Marx et al 2005;Oliver et al 2007;Poll et al 2003;Sessitsch et al 2001;Stemmer et al 1998;Yeager and Sinsabaugh 1998). And these studies revealed that the degree of humification increases with a decrease in particle size fractions, while the turnover rate and C/N ratio decreases (Aita et al 1997;Marx et al 2005;Stemmer et al 1998).…”
Section: Introductionmentioning
confidence: 99%